2014
DOI: 10.12691/ajssm-2-5a-7
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate and Blood Pressure Trait of Bangladeshi Children Age Ranged from 1 to 12 Years

Abstract: Blood pressure of Bangladeshi children aged between 1 to 12 from both sexes were measured in Bangladesh. Three hundred and seventy one children were measured randomly for their heart rate and blood pressure, out of which 243 were boys and 128 were girls. In the present study height and weight were increased gradually as age increases. Both systolic and diastolic pressure elevated gradually as age advanced though the change was not highly significant. Similar observations were also noticed when both boys and gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…On comparing our data with the work of O’Leary et al we found lower values for the resting HR quantified by the 50th percentile. One possible explanation could be the anxiety associated to the visit to Emergency Department in the study of O’Leary et al Adhikar et al [ 13 ] studied 371 children aged 1 to 12 years old from Bangladesh (243 males and 128 females) and found significant correlation between age and HR both in male and female individuals: r bo−0.9 for age versus HR in all the study population; r in−0.89 for boys and r .8−0.89 for girls. A significant correlation between HR and W or H is also stated in their study, R is0.90 for HR versus W, and R a0.84 for HR versus H in males and R H0.88 for HR versus W and R W0.81 for HR versus H in females.…”
Section: Discussionmentioning
confidence: 99%
“…On comparing our data with the work of O’Leary et al we found lower values for the resting HR quantified by the 50th percentile. One possible explanation could be the anxiety associated to the visit to Emergency Department in the study of O’Leary et al Adhikar et al [ 13 ] studied 371 children aged 1 to 12 years old from Bangladesh (243 males and 128 females) and found significant correlation between age and HR both in male and female individuals: r bo−0.9 for age versus HR in all the study population; r in−0.89 for boys and r .8−0.89 for girls. A significant correlation between HR and W or H is also stated in their study, R is0.90 for HR versus W, and R a0.84 for HR versus H in males and R H0.88 for HR versus W and R W0.81 for HR versus H in females.…”
Section: Discussionmentioning
confidence: 99%